Studi Penyimpanan Massa Biogas Dengan Menggunakan Karbon Aktif Hasil Dari Proses Steam Activation Dengan Variasi Suhu Karbonisasi - Suarjana, I Putu Ngurah; Wijaksana, Hendra; Sucipta, Made (Teknik Desain Mekanika, 2022)
Abstract Simantri is an innovation that develops technology that innovates the community for village progress. Simantri activities include increasing the number of livestock populations, planting area, and the quality of the products produced. Cow dung waste from Simantri can be used as biogas as fuel to turn on the stove. The use of biogas for the wider community has not been optimal due to the limited distribution of biogas. This research is expected to find out the potential utilization of rice straw waste as an adsorbent as a biogas storage medium with the ANG (Adsorbtion Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 Psi with 70 grams of bamboo betung activated carbon as the adsorbent, the activated carbon was varied with carbonization temperatures of 425oC, 525oC, 725oC at an activation steam temperature of 625oC using a mass flow rate of 0.050kg/s water and using a mesh. 35-45. The results of the study in biogas storage showed that the highest mass absorption occurred at a carbonization temperature variation of 725oC which was able to store 36.8 grams of biogas. Then for testing biogas levels, the highest levels of methane and the lowest carbon dioxide occurred at variations in carbonization temperature of 425oC with a weight capable of storing 28.2 grams. Keywords: bamboo betung, biogas, ANG, Carbon Active, carbonization temperature